2014
DOI: 10.1002/jcop.21658
|View full text |Cite
|
Sign up to set email alerts
|

Social Connectedness Among Lesbian, Gay, Bisexual, and Transgender Parents Living in Metropolitan and Regional and Rural Areas of Australia and New Zealand

Abstract: with those living in outer metropolitan and regional and rural areas. We also look at experiences of discrimination and being out about sexuality in various community settings. Data for this article were drawn from the Work, Love, Play study of 455 Australian or New Zealand LGBT parents. Over half the participants lived in outer metropolitan or regional and rural areas. Parents living in outer metropolitan or regional and rural areas were less likely than those living in the inner city to feel connected to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Due to this association and the multicollinearity it introduces into the model, when the urbanicity × family type and political leaning × family type interactions are both included in the model, neither interaction is significant, but both are significant on their own. The choice was made to include only the urbanicity × family type interaction in the final model, in part because Power et al (2014) examined urbanicity specifically. The main effect of political leaning is still included, and thus the effects of urbanicity reported in the main text are controlling for the percentage of the community voting Democratic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this association and the multicollinearity it introduces into the model, when the urbanicity × family type and political leaning × family type interactions are both included in the model, neither interaction is significant, but both are significant on their own. The choice was made to include only the urbanicity × family type interaction in the final model, in part because Power et al (2014) examined urbanicity specifically. The main effect of political leaning is still included, and thus the effects of urbanicity reported in the main text are controlling for the percentage of the community voting Democratic.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior work (Wainright and Patterson, 2006;Rivers et al, 2008), there were no differences overall in the level of victimization that children reportedly experienced, by family type. However, our investigation of community level variables that have rarely been explored (Power et al, 2014) suggests that the relationship between family structure and victimization may depend on where families live.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lena Dominelli states that the "identity of the individual, whether as subject or object of other people's definitions, is enacted through the social relations in which they both engage" (2002, p. 40). To be lesbian but not to be recognized as lesbian can be a stressor (see Power et al, 2014) and research has shown, that for women, being "out" is associated with mental well-being (Pachankis, Cochran, & Mays, 2015). This makes it unfortunate that the sexual identities of the SLMs in particular were obscured by others' heteronormative presumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Research specific to LGBTQ parents has indicated that social support is important to their well-being (Goldberg & Smith, 2008;Goldberg & Smith, 2011;Ross, 2005) and, for couples, facilitates relationship satisfaction (Blair & Holmberg, 2008;Sumontha, Farr, & Patterson, 2016;Vyncke & Julien, 2007). Outside of urban areas, however, with their greater concentrations of LGBTQ individuals, it can be difficult to find such support, especially at the institutional level (Holman & Oswald, 2011;Power et al, 2014).…”
Section: Introductionmentioning
confidence: 99%